Kultura organizacyjna w agencjach regulacyjnych Unii Europejskiej - Kohtamäki, Natalia (Polski Przegląd Stosunków Międzynarodowych, 2018)
Organizational Culture in the EU Regulatory Agencies Organizational culture means a set of values, norms, symbols, customs and traditions. In consequence it affects the interpretation of reality by employees of the organization, their behavior and impact in relation to other entities. It is also an important foundation in the process of building institutional identity. The problematic of organizational culture is a field of interest for specialists representing many different scientific disciplines. Especially private organizations, such as multicultural, transnational and transboundary active corporations undergone multiple detailed analysis both in international and in Polish context. The organizational culture of the EU regulatory agencies, by contrast, has not been analyzed yet in-depth. The article aims to explain the most important problems connected with this topic with special emphasis on the inter-governmental structure of these bodies.